Community Involvement in Management Environmental Impact Analysis Perspective - Siska Dindari; Agus Silaen Tampubolon (Journal of Global Islamic Economic Studies, 2024)
The environment is a spatial unit consisting of all objects, powers, circumstances, and living things including humans and their behavior. community involvement in environmental management from an environmental impact analysis (ADL) perspective. Community involvement is an important element in the success of environmental policies, as they are often the most affected. Through qualitative methods, this study analyzes various forms of community participation in several regions, including in the planning, implementation, and evaluation of environmental programs. The results show that community involvement not only increases the effectiveness of the program, but also facilitates the identification of relevant local issues. In addition, the active participation of the community contributes to increasing environmental awareness and encourages local initiatives for the conservation of natural resources. This study recommends that stakeholders strengthen communication and collaboration with communities, as well as provide adequate training and resources to increase their capacity in environmental management. Thus, an inclusive ADL approach can result in more sustainable and responsive solutions to the needs of local communities.